Beyond the Feeling Individual: Insights from Sociology on Emotions and Embeddedness - Zhang, Rongrong; Voronov, Maxim; Toubiana, Madeline; Vince, Russ; Hudson, Bryant Ashley (Journal of Management Studies, 2024)
AbstractOrganizational scholars have treated emotions mostly as an individual‐level phenomenon, with limited theorisation of emotions as an important component in social embeddedness. In this review essay, we argue for the need for a toolkit to study emotions as an inherently social phenomenon. To do so, we apply insights from sociology that have been under‐utilized in management and organization research. We focus on three sociological concepts: collective emotions and social bonds, emotional energy and moral batteries, and emotional capital. We then develop an integrative model of emotional embeddedness to emphasize that emotions are socially constructed and socially authorized. We end the paper by setting out a research agenda for more research in management and organization that is informed by these three concepts.